Pengaruh Penggunaan E-Commerce, Pengetahuan Kewirausahaan dan Motivasi Berwirausaha terhadap Minat Berwirausaha: Penelitian - Nadiyah Safira; Retno Mustika Dewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of e-commerce usage, entrepreneurial knowledge, and entrepreneurial motivation on entrepreneurial interest. This study used a sample of 57 grade XI students of SMAS Semen Gresik with a causal associative research method with a quantitative approach. The research instrument was a questionnaire that had been tested for validity and reliability. The data analysis technique used was multiple linear regression analysis assisted by IBM SPSS software. The results showed that motivation for entrepreneurship, knowledge of entrepreneurship, and the use of e-commerce simultaneously influenced entrepreneurial interest. Thus, although the school tries to provide support in entrepreneurship learning, it cannot be denied that the current entrepreneurial motivation.